PENGARUH HARGA DAN KUALITAS PELAYANAN KARYAWAN FRONT OFFICE DEPARTMENT TERHADAP KEPUASAN PELANGGAN MENGINAP DI HOTEL PUSAKO BUKITTINGGI - Sintia, Nelvi; Kasmita, Kasmita; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
The purpose of this study is to analyze the influence of price and qualityof front office employees service to customer satisfaction os staying at Hotelpusako Bukittinggi. This research is correlation. The population in this study isamount 1025. Selection of informants using purposive sampling technique asmany as 92 people. Data collection using questionnaires based on Likert Scalethat has been tested for its validity and reliability. Based on research result ofroom price in Hotel Pusako Bukittinggi classified as less good (53%), quality offront office employees service at Hotel Pusako Bukittinggi classified as less good(53%), Customer satisfaction staying at Hotel Pusako is classified as less good(64%). The results showed that there is a positive and significant influencebetween the price and quality of front office employees service to the satisfactionof customers staying at Pusako Bukittinggi with an influential contribution of27,7%.Keywords: Price, Service Quality and customer Satisfaction.